Role of the Dynorphin/Kappa Opioid Receptor System in the Motivational Effects of Ethanol. (5th June 2017) - Anderson, Rachel I.; Becker, Howard C.
Abstract : Evidence has demonstrated that dynorphin (DYN) and the kappa opioid receptor (KOR) system contribute to various psychiatric disorders, including anxiety, depression, and addiction. More recently, this endogenous opioid system has received increased attention as a potential therapeutic target for treating alcohol use disorders. In this review, we provide an overview and synthesis of preclinical studies examining the influence of alcohol (ethanol [EtOH]) exposure on DYN/KOR expression and function, as well as studies examining the effects of DYN/KOR manipulation on EtOH's rewarding and aversive properties. We then describe work that has characterized effects of KOR activation and blockade on EtOH self‐administration and EtOH dependence/withdrawal‐related behaviors. Finally, we address how the DYN/KOR system may contribute to stress–EtOH interactions. Despite an apparent role for the DYN/KOR system in motivational effects of EtOH, support comes from relatively few studies. Nevertheless, review of this literature reveals several common themes: (i) rodent strains genetically predisposed to consume more EtOH generally appear to have reduced DYN/KOR tone in brain reward circuitry; (ii) acute and chronic EtOH exposure typically up‐regulate the DYN/KOR system; (iii) KOR antagonists reduce behavioral indices of negative affect associated with stress and chronic EtOH exposure/withdrawal; and (iv) KOR antagonists are effective in reducing EtOH consumption, but are often more efficacious under conditions that engender high levels of consumption, such as dependence or stress exposure. These results support the contention that the DYN/KOR system plays a significant role in contributing to dependence‐ and stress‐induced elevation in EtOH consumption. Overall, more comprehensive analyses (on both behavioral and mechanistic levels) are needed to provide additional insight into how the DYN/KOR system is engaged and adapts to influence the motivation effects of EtOH. This information will be critical for the development of new pharmacological agents targeting KORs as promising novel therapeutics for alcohol use disorders and comorbid affective disorders. Abstract : The kappa opioid receptor (KOR) system, which is typically upregulated by stress and ethanol exposure, has received recent attention as a potential therapeutic target for alcoholism. Review of the literature reveals that KOR antagonists reduce negative affect associated with stress and ethanol exposure/withdrawal. Further, KOR antagonists are effective in reducing ethanol consumption, but are often more efficacious under conditions that promote elevated drinking. These results support a role for the KOR system in contributing to dependence‐ and stressinduced ethanol consumption.